Studies in Protective Coatings of Metals with Special Reference to Organic Inhibitors Mixed with Polyurethane - M. AGRAWAL, REETA; R. CHOUREY, VIJAY; GARG, S.L. (Asian Journal of Chemistry, 2010)
The inhibition of corrosion of steel strips and aluminium strips in different chemical medium and atmosphere have been studied by immersion method. In this investigation, resorcinol and furfural have been tested as corrosiion inhibitors for aluminium and steel strips. These organic compounds have been used by mixing with protective coating material like polyurethane. The study shows that these compounds act as a good corrosion inhibitors with an efficiency which reaches from 40 to 90 % in different environment. The inhibition action of these compounds seems to be due to their adsorption on the metal surface, hence blocking the available area for corrosion.